Preceptorship in a Hospital Residency Program: meanings and contributions from the perspective of preceptor nurses (Research, Society and Development, 2022)
The Health Residency Programs are a lato sensu postgraduate modality characterized by in-service training, highlighting the qualification of professionals to work in the job market. In this context, this study aimed to characterize the profile, meanings and contributions of the preceptor in the training process of the Residency in Health, from the perspective of preceptors of a Nursing Residency Program. This is an exploratory, descriptive, quantitative study carried out in a hospital in Recife, Pernambuco, Brazil. Sampling was stratified and statistical analysis was performed using the Statistical Package for Social Sciences® (SPSS), version 18.0. The results showed that the profile of preceptors was predominantly composed of women, aged over 40 years, specialists. The preceptor was conceptualized as the professional, linked to the health institution that offers the Residency Program, who accompanies the resident in his practical activities. Potentialities and weaknesses were identified in the preceptorship development process. The main contributions of the preceptors in the training process were the teaching of technical procedures and the performance of evaluation based on the theoretical-practical content assimilated by the residents. Thus, this study highlights the importance of preceptorship in Nursing in the professional training of residents, which is perpetuated as the main strategy in the training process in the Residence.